2022
DOI: 10.1590/1806-9061-2021-1578
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks to Predict Egg-Production Traits in Commercial Laying Breeder Hens

Abstract: In recent years, egg production has had an intense growth in Brazil, and Brazilian egg consumption per capita has significantly increased in the last decade. To reduce sanitary and financial risks, decisions regarding the production and health status of the flock must be made based on objective criteria. Our aim was to determine the main "input" variables for the prediction of egg production performance in commercial laying breeder flocks using an ANN model. The software NeuroShellClassifier and NeuroShell Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(62 reference statements)
0
3
0
2
Order By: Relevance
“…Vale ressaltar que todas as variáveis também podem ser listadas como variáveis de saída. Essa escolha depende das necessidades da empresa (9,10) . As variáveis selecionadas como dados de "saída" neste estudo foram consideradas entre os resultados mais importantes a serem previstos de acordo com a empresa avícola avaliada.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Vale ressaltar que todas as variáveis também podem ser listadas como variáveis de saída. Essa escolha depende das necessidades da empresa (9,10) . As variáveis selecionadas como dados de "saída" neste estudo foram consideradas entre os resultados mais importantes a serem previstos de acordo com a empresa avícola avaliada.…”
Section: Resultsunclassified
“…Estudos anteriores conduzidos por nosso grupo de pesquisa demonstraram que a RNA pode ser usada para o gerenciamento de parâmetros de desempenho em diferentes áreas da produção avícola (3,(7)(8)(9)(10) . Além disso, a RNA tem sido utilizada para avaliar a depleção de linfócitos na bolsa de Fabricius e no timo (3,11,12) .…”
Section: Introductionunclassified
“…It is noteworthy that all variables can also be listed as output variables. This choice depends on the needs of the company (9,10) . The variables selected as "output" data in this study were considered among the most important results to be predicted according to the poultry company evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies conducted by our research team showed that ANN can be used for performance parameter management in different areas of poultry production (3,(7)(8)(9)(10) . Furthermore, ANN has been used to evaluate lymphocyte depletion in the bursa of Fabricius and thymus (3,11,12) .…”
Section: Introductionmentioning
confidence: 99%
“…A study done in Brazil examined the application of an ANN model for predicting egg production performance in commercial laying breeder flocks. For this purpose, 26 characteristics of egg production were selected as input variables for the model [8]. From a study conducted in Japan with the aim of predicting the cumulative egg production of Japanese quail using linear regression, partial linear regression, and multivariate adaptive regression algorithms, included variables such as age at sexual maturity, weight at sexual maturity, average weight of the first ten eggs [9].…”
Section: Related Workmentioning
confidence: 99%